PENGKAJIAN PENGGUNAAN PAKAN LOKAL PADA AYAM PEDAGING BERDASARKAN KUALITAS KARKAS, PERTUMBUHAN DAN BIAYA - Irine Praptiwi (AGRICOLA, 2012)
Assesment was conducted to determine the influence of the use of local feed about carcass quality, growth and efficiency the cost of the chicken conservation. Assesment was done by using descriptive analysis of the 30 chickens that were divided to 4 treatment. Analysis were perfomed using the questioner, observation and weighing, while the cost analysis obtained by calculating the cost of production and income.  Results from this assesment indicates that the quality of carcass, growth and cost efficiency are best seen in the treatment chickens group 2, used combination of local food and feed from the outside.